ETHICAL PERCEPTIONS OF TAX EVASION AMONG CHINESE PROFESSIONALS: A STUDY OF DETERMINANTS AND IMPLICATIONS - Kok Loang; Shi Yang (International Journal of Accounting, Finance and Business, 2024)
The government relies on tax income to grow and sustain the nation. Therefore, its deterioration hurts the economy. China adopted the Self-Assessment System (SAS) to tackle tax evasion. SAS taxpayers must make ethical and legal decisions to participate in the tax system. Tax research has identified taxpayer beliefs and ethics as significant factors in tax evasion. However, few studies have examined taxpayers' ethical views on tax evasion and the variables influencing them. Thus, this study replicates previous research on ethics and tax evasion to understand Chinese professionals' perceptions and reasoning on ethics and tax evasion and to examine the determinants (personal and professional attributes) of ethical perception. Professional groups from accounting, law, engineering, and medicine in Klang Valley were surveyed. The chosen Chinese experts saw tax avoidance as ethically justifiable in certain situations. Misappropriating tax funds was the most robust basis for tax evasion. In addition to the two perceptual dimensions of ethics to tax evasion reported in Western nations, this study discovered a selfish motivations component in China. Tax evasion ethics were also impacted by Chinese professionals' features (demographics and personality factors) and professional attributes (e.g. code of ethics). Thus, tax authorities and professional organisations should prioritise ethical education and target populations that need more tax education to increase voluntary tax compliance.